Phase 1 Clinical Trial of a Replication-Defective Human Cytomegalovirus (CMV) Vaccine. (4th October 2017) - Adler, Stuart; Lewis, Nicole; Conlon, Anthony; Christiansen, Mark; Al-Ibrahim, Mohamed S; Rupp, Richard; Fu, Tong Ming; Bautista, Oliver; Tang, Huaping; Culp, Timothy; Das, Rituparna; Beck, Karen; et al.
Abstract: Background: Congenital CMV remains an unmet medical need worldwide. Naturally acquired CMV immunity in women prior to pregnancy has been shown effective in reducing maternal-fetal transmission. V160 is engineered as a replication-defective CMV, and its replication in culture is controlled by a synthetic chemical. V160 can't replicate in humans but it maintains all virological properties for presentation of viral antigens, including gH/gL/pUL128-131 pentameric complex, important for potent neutralizing antibodies (NABs). Methods: Approximately 190 CMV seronegative and seropositive adults at study entry received 3 doses of V160 or placebo administered via intramuscular (IM) or intradermal (ID) route on Day 1, Month 1, and Month 6. Four antigen levels (10, 30, 100, and 250 units per dose) formulated with or without aluminum phosphate adjuvant were evaluated. In each vaccination group, approximately 10 and 4 subjects received study vaccine and placebo, respectively. Injection site and systemic adverse events (AEs) were collected for 14 days after each vaccination. Serious AEs (SAEs) were assessed up to Month 18. Viral shedding (urine and saliva) were monitored up to Month 12. CMV-specific NABs and cell-mediated immune responses (CMI) were measured prior and 1 month after each vaccination, and at Months 12 and 18. Results: During the study, no serious AEs were reported and only one CMV seropositive subject had non-vaccine type viral shedding. In both seronegative and seropositive cohorts, proportion of subjects who reported injection site AEs was higher in V160 recipients than placebo controls. Proportion of subjects who reported systemic AEs was comparable across V160 doses/formulations and placebo. In the CMV seronegative cohort, immune responses increased with incremental dosing. More importantly, recipients of V160 from several dose levels mounted NAB and CMI responses at 1 month post dose 3 (PD3) that were comparable to baseline levels measured in seropositive subjects. Conclusion: V160 had acceptable safety profile across all dose levels and formulations studied; Vaccine was immunogenic and elicited NAB and CMI responses at 1 month PD3 that were comparable to natural CMV infection. Disclosures: S. Adler, Merck: Investigator, Research grant. N. Lewis, Merck: Employee, Salary. A. Conlon, Merck: Employee, Salary. M. Christiansen, Merck: Investigator, Research grant. M. S. Al-Ibrahim, Merck: Investigator, Research grant R. Rupp, Merck: Investigator, Research grant. T. M. Fu, Merck: Employee, Salary. O. Bautista, Merck: Employee, Salary. H. Tang, Merck: Employee, Salary.T. Culp, Merck: Employee, Salary. R. Das, Merck: Employee, Salary. K. Beck, Merck: Employee, Salary. G. Tamms, Merck: Employee, Salary. L. Musey, Meck: Employee, Salary.